The silence is broken, the stage is set. Black Tickle, 1988. Raw footage. Tape 03 - Memorial University of Newfoundland. Division of Extension Service (Memorial University of Newfoundland. Division of Extension Service, 1988)
Raw footage for the film "The Silence is Broken, the Stage is Set : the 1988 Fishery at Black Tickle Problems and Solutions." Minor distortion throughout.